Soil mineralogical and nutrient characteristics of forest islands and surrounding ecosystem types in West Africa suggest anthropogenic soil improvement - Mesele, S.A.; Melenya, C.; Bougma, A.; Azeez, J.; Ajiboye, G.A.; Dubbin, W.; Logah, V.; Compaore, H.; Veenendaal, E.M.; Lloyd, J. (Springer, 2024)
Aims Ecosystem changes in the mesic savannas of West Africa are resulting in the formation of patches of ‘forest islands’ around local communities in an otherwise open savanna landscape. There have been conflicting reports on the origin of these forest islands with a very limited understanding of their biogeochemistry. This study evaluated the soil mineralogical and chemical characteristics of forest islands and their surrounding ecosystems comprising croplands and open savannas in Burkina Faso, Ghana, and Nigeria to provide information on the processes leading to the formation of forest islands.